FACTORS INFLUENCING THE PRICE OF INDONESIA SOVEREIGN SUKUK IN SECONDARY MARKET - Muhammad Fatih Al Aziz; Irfan Syauqi Beik; Achmad Firdaus (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2019)
The paper analyses four influencing factors toward the Indonesian sovereign sukuk price in the secondary market during the period January 2015 to June 2018, namely liquidity, coupon, maturity and the Indonesia composite index (ICI). The model used is multiple linear regression analysis with time series data obtained from the Ministry of Finance of Indonesia. The results of the analysis show that liquidity had a significant positive effect on the sovereign sukuk price in the secondary market, that coupon also had a significant positive effect; maturity had a significant negative effect, while the Indonesia composite index had a significant positive effect.==============================================================================================Faktor-faktor yang Mempengaruhi Harga Sukuk Indonesia di Pasar Sekunder. Makalah ini menganalisis empat faktor yang mempengaruhi harga sukuk Indonesia di pasar sekunder selama periode Januari 2015 hingga Juni 2018, yaitu likuiditas, kupon, jatuh tempo dan indeks harga saham gabungan (IHSG). Model yang digunakan adalah analisis regresi linier berganda dengan data deret waktu diperoleh dari Kementerian Keuangan Indonesia. Hasil analisis menunjukkan bahwa likuiditas berpengaruh positif signifikan terhadap harga sukuk negara di pasar sekunder, kupon juga berpengaruh positif signifikan, maturitas berpengaruh negatif signifikan, sedangkan indeks harga saham Indonesia berpengaruh positif signifikan terhadap harga sukuk Negara di Pasar Sekunder